Pneumonia associated with mechanical ventilation in intensive care units (Research, Society and Development, 2022)
Objective:To analyze nursing actions against VAP in the context of intensive care. Method: This study is classified as descriptive, the integrative literature review was adopted as an instrument. Sixteen files were selected between the years 2016 to 2021 in the SciELO, Medline, BDENF and Lilacs databases, using the Health Sciences Descriptors: Pneumonia associated with Mechanical Ventilation, Intensive Care Unit and Nursing. Results: Some studies have pointed out that prolonging the duration of mechanical ventilation and, consequently, the length of stay increases the risk of developing pneumonia associated with mechanical ventilation, they also reinforce that the role of nursing is essential in the elaboration of care plans, as it aims to reduce the severity and lethality of complications. Conclusion: It is understood that VAP is considered a public health problem, which generates significant impacts on the health of patients. Thus, knowing the clinical characteristics of patients can support actions that will help intensive care professionals, especially nurses, in the elaboration of care plans, aiming at reducing the severity and lethality of complications.